Evaluasi Deteksi Posisi Kereta Menggunakan Radio Ranging di CBTC - Copa Rivabillah; Wahyu Kusuma Raharja (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
This study analyzes the performance of Radio Ranging technology in improving train position detection accuracy within the Communications-Based Train Control (CBTC) system of MRT Jakarta. The simulation-based experimental method was carried out using MATLAB, with the comparison of Radio Ranging and Tachogenerator (TG) across three operational conditions: open area, tunnel, and dense urban environment. Evaluation metrics include position deviation and Root Mean Square Error (RMSE). The results show that Radio Ranging provides better accuracy compared to TG, particularly in tunnel and dense areas, where TG tends to accumulate errors. These findings indicate that Radio Ranging can serve as a complementary method to enhance CBTC reliability and operational safety of MRT Jakarta.